2015
DOI: 10.1016/j.ijms.2014.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Ion mobility and tandem mass spectrometry of phosphatidylglycerol and bis(monoacylglycerol) phosphate (BMP)

Abstract: The tandem mass spectrometry, ion mobility, and normal phase HPLC of isomeric phosphatidylglycerol (PG) and bis(monoacylglycerol)phosphate (BMP) have been investigated in this study with the objective of differentiating these unique classes of lipids. Measurement of ion mobility using the traveling wave method for negative molecular and product ions from isomeric PG and BMP yielded identical results, but different ion mobilities were observed for positive product ions arising from collision-induced dissociatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…However a review of the biomedical literature to relate these findings to biological significance, indicated that isobaric bis(monoacylglycero)phosphate (BMP) lipids share exact molecular formulas with these PG lipid species 49 (Supplement Table 1 ). Differentiation of structural isomers that are exact isobars such as PG and BMP lipids is challenging 50 .
Figure 3 MALDI mass spectra taken from a single pixel in the RPE region of tissue from ( a ) Abca4 −/− and ( b ) Sv129 mouse tissue.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However a review of the biomedical literature to relate these findings to biological significance, indicated that isobaric bis(monoacylglycero)phosphate (BMP) lipids share exact molecular formulas with these PG lipid species 49 (Supplement Table 1 ). Differentiation of structural isomers that are exact isobars such as PG and BMP lipids is challenging 50 .
Figure 3 MALDI mass spectra taken from a single pixel in the RPE region of tissue from ( a ) Abca4 −/− and ( b ) Sv129 mouse tissue.
…”
Section: Resultsmentioning
confidence: 99%
“…MS/MS analysis in negative ion mode can confirm the fatty acid chain structures, but it cannot clearly differentiate PG from BMP lipids. Therefore, PG and BMP lipid standards were analyzed using reverse phase LC-MS/MS in both negative ion mode (to identify the fatty acid chains) and positive ion mode (to confirm the sn configuration of the fatty acid chains) 50 , 52 , 53 . The method was optimized to ensure chromatographic separation of the two commercially available standards [PG(18:1_18:1) and BMP(18:1_18:1)] and to confirm fragmentation patterns could be used to discern the isobaric species.…”
Section: Resultsmentioning
confidence: 99%
“…PGs, on the other hand, are thought to have antiviral properties, inhibiting viral proliferation in the lungs including respiratory syncytial virus. 58,59 Sn-positional isomers are particularly challenging to characterize as collision-based tandem mass spectrometry methods produce spectra with only differences in ion abundances, i.e, nonunique identifying ions. 59 To evaluate MALDI TIMS as a platform to separate PG and BMP isomers, mobility data was collected for the standards PG (14:0/14:0) and BMP (14:0/14:0) ( Figure 3A).…”
Section: Sn-positionmentioning
confidence: 99%
“…34 This is consistent with previous findings showing that PGs have more compact structures than the BMPs. 34,59 A 1:1 mixture was analyzed to evaluate the separation of the isomers. An extracted ion mobilogram was generated for the deprotonated species (m/z 665.49), and two peaks could be resolved in the mobilogram (1.290 and 1.299).…”
Section: Sn-positionmentioning
confidence: 99%
See 1 more Smart Citation